Women in Medieval History and Historiography - Stuard, Susan Mosher (Philadelphia, Pa. : University of Pennsylvania Press, 2016)
What was the status of women in the Middle Ages? How have women fared in the hands of historians? And, what is the current state of research about women in the Middle Ages? Susan Mosher Stuard and contributors address these questions.
Frontmatter -- Contents -- Introduction -- 1. Golden Ages for the History of Medieval English Women -- 2. Invisible Madonnas? The Italian Historiographical Tradition and the Women of Medieval Italy -- 3. Fashion's Captives: Medieval Women in French Historiography -- 4. A New Dimension? North American Scholars Contribute Their Perspective -- 5. A Documented Presence: Medieval Women in Germanic Historiography -- Bibliographies -- Index -- Contributors
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Dec. 09, 2016).
JSTOR
Keywords: Women -- History -- Middle Ages, 500-1500.; Social history -- Medieval, 500-1500.; Women historians; Femmes -- Histoire -- 500-1500 (Moyen Âge); Histoire sociale -- 500-1500 (Moyen Âge); Historiennes; historians; HISTORY -- Historiography; Social history -- Medieval; Women historians; Women -- Middle Ages; 500-1500; History